Assessing the Potential of Gallic Acid and Methyl Gallate to Enhance the Efficacy of _-Lactam Antibiotics against Methicillin-Resistant Staphylococcus aureus by Targeting _-Lactamase: In Silico and In Vitro Studies - Pimsumon Jiamboonsri; Chatchakorn Eurtivong; Sompit Wanwong (My University, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA), a global health concern, has prompted research into antibiotic adjuvants as a potential solution. Although our group previously reported the enhancing effects of gallic acid (GA) and methyl gallate (MG) on penicillin G activity against MRSA, the synergistic potential with other β-lactam antibiotics and the underlying mechanism have not been fully explored. Therefore, this study primarily aimed to investigate the antibacterial synergism with β-lactam antibiotics through disc diffusion, checkerboard, and time–kill assays. The β-lactamase inhibition was also examined through both molecular modeling and in vitro experiments. Additionally, bacterial morphology changes were studied using a scanning electron microscopy (SEM). The results revealed that both GA and MG exhibited anti-MRSA activity and showed indifferent effects when combined with β-lactam antibiotics against methicillin susceptible S. aureus (MSSA). Interestingly, MG demonstrated synergism with only the β-lactamase-unstable antibiotics against MRSA with the lowest fractional inhibitory concentration (FIC) indexes of ≤3.75. However, GA and MG exhibited weak β-lactamase inhibition. Furthermore, GA, MG, and the combination with ampicillin induced the morphological changes in MRSA, suggesting a possible mechanism affecting the cell membrane. These findings suggest that MG could potentially serve as an adjunct to β-lactam antibiotics to combat MRSA infections.
Keywords: Penicillin binding proteins; Lactam; Antibiotic Resistance in Bacteria